2022
DOI: 10.3390/biom12030387
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Signaling for TOR in Eukaryotes: Sensors, Transducers, and a Sustainable Agricultural fuTORe

Abstract: Eukaryotic cells monitor and regulate metabolism through the atypical protein kinase target of rapamycin (TOR) regulatory hub. TOR is activated by amino acids in animals and fungi through molecular signaling pathways that have been extensively defined in the past ten years. Very recently, several studies revealed that TOR is also acutely responsive to amino acid metabolism in plants, but the mechanisms of amino acid sensing are not yet established. In this review, we summarize these discoveries, emphasizing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 110 publications
0
9
0
Order By: Relevance
“…Sestrin 2-GATOR2-GATOR1-RagB signaling mediates the stress-dependent suppression of mTORC1 activity [ 394 ]. Sestrins function as guanine nucleotide dissociation inhibitors for Rag GTPases to control mTORC1 signaling [ 395 ] and regulate the localization of mTORC1 in response to amino acids [ 396 , 397 ].…”
Section: Perinatal Factors Disturbing Mex Mir-regulated β Cell Homeos...mentioning
confidence: 99%
“…Sestrin 2-GATOR2-GATOR1-RagB signaling mediates the stress-dependent suppression of mTORC1 activity [ 394 ]. Sestrins function as guanine nucleotide dissociation inhibitors for Rag GTPases to control mTORC1 signaling [ 395 ] and regulate the localization of mTORC1 in response to amino acids [ 396 , 397 ].…”
Section: Perinatal Factors Disturbing Mex Mir-regulated β Cell Homeos...mentioning
confidence: 99%
“…One major way of amino acid signaling is mediated by amino acid-binding proteins, including enzymes, transporters, tRNA ( 112 ). For instance, target of rapamycin was recently reported to be activated by amino acids ( 116 ). As such, Ding et al demonstrated that amino acids could function as specific and selective signaling molecules ( 117 ).…”
Section: Amino Acids As Signaling Molecules In T Cellsmentioning
confidence: 99%
“…1). Although RAGs are conserved in mammals and yeast (Nicastro et al ., 2017; Liu & Sabatini, 2020), both transducers and the proposed AA sensors are missing in plants and green microalgae (Liu & Xiong, 2022; Lutt & Brunkard, 2022; Mallén‐Ponce et al ., 2022a), suggesting that nutrient availability is signaled to TORC1 in these organisms through different mechanism(s).…”
Section: Control Of Torc1 By Amino Acidsmentioning
confidence: 99%